Budget performance evaluation of public hospitals based on Entropy-Weighted TOPSIS Model - Li, Huilin; Mercado, Cecilia A. (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2024)
Recovery Version (See for detail) In order to objectively assess the budget performance of public hospitals, this paper have utilized budget performance data from nine public hospitals in Shenzhen from 2019 to 2021 and employ the TOPSIS comprehensive evaluation method based on Entropy weight. The analysis will provide rankings for the budget performance of these hospitals. The results indicate that the top three ranked hospitals are tertiary (A) public hospitals, demonstrating relatively sound budget performance, while the bottom three ranked hospitals are primary (C) public hospitals, indicating extremely poor budget performance. Thus, the budget performance of public hospitals tends to be positively correlated with their overall strength. Further investigation reveals an imbalance in resource allocation among public hospitals, necessitating corresponding measures to promote their coordinated development. Article Information: Received 4/25/2024 / Revised 5/24/2024 / Accepted 5/26/2024 / Online First 6/4/2024